Visualizing the recovery of patients in Critical Care Units. (July 2023) - Stuart, Liz; Haynes, Christopher; Tantam, Kate; Gardner, Roger; Palomino, Marco A
This paper presents a detailed case study of the application of techniques from Information Visualization to data collected in Critical Care Units (CCUs). This data is heterogeneous and sometimes incomplete due to the pressures on staff in the environment. Thus, it can be difficult to use conventional means to visualize it meaningfully. The paper presents the software tool called CCViews. It was developed to support visualization of CCU data. It enables clinicians to view the trajectory of patient recovery and track the effectiveness of different interventions such as physiotherapy. Note that this work is underpinned by the world-famous information seeking mantra, which emphasizes the need to provide users with views of their data at differing levels of granularity.